LGBT rights in Africa - Lise Rakner (Edward Elgar Publishing, 2020)
This innovative and thought-provoking Research Handbook explores not only current debates in the area of gender, sexuality and the law but also points the way for future socio-legal research and scholarship. It presents wide-ranging insights and debates from across the globe, including Africa, Asia, Eastern Europe and Australia, with contributions from leading scholars and activists alongside exciting emergent voices.